Bariatric Surgery, Safety and Type 2 Diabetes - Spanakis, Elias; Gragnoli, Claudia (Obesity surgery, 2009)
Obesity and type 2 diabetes (T2D) represent major health concerns in the USA. Weight loss is the most important aspect in T2D management, as it reduces both morbidity and mortality. Available lifestyle, behavioral, and pharmacological strategies provide just mild to moderate weight loss. The greatest degree of T2D prevention or T2D amelioration in obese subjects has been reported in subjects who underwent bariatric surgery. In the current review, we will describe various types of bariatric surgery, related safety profiles, and their effect on T2D, as well as the potential mechanisms involved in the remission of T2D. Finally, we hereby examine whether bariatric surgery may be considered a treatment for T2D in pregnant women, children, adolescents and subjects at least 65 years old.